2009
DOI: 10.1016/j.anl.2008.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The first case of osteoma in the false vocal fold

Abstract: Objectives-This article reports the first evidence of a larynx osteoma of the false vocal fold.Study design-Case report and literature review.Methods-Case report and review of previously published cases of larynx osteomas.Results-A 79 year-old patient was referred to our institution for dysphagia and hoarseness. Fibrolaryngoscopy showed a regular surface tumefaction of the false fold and the left ventricle, with preserved cordal motility. Patient underwent direct laryngoscopy with CO 2 laser excision of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Osteoma in the bone marrow cavity is termed bone marrow osteoma. Various studies have reported that osteomas may exist in multiple unusual regions, including the acoustic meatus ( 10 ), middle ear ossicles ( 11 ) and false vocal folds ( 12 ). Notably, whether osteoma may occur in the bone marrow remains unclear, however, this study presented the case of a patient with bone marrow osteoma located in the tibia that underwent surgical excision of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoma in the bone marrow cavity is termed bone marrow osteoma. Various studies have reported that osteomas may exist in multiple unusual regions, including the acoustic meatus ( 10 ), middle ear ossicles ( 11 ) and false vocal folds ( 12 ). Notably, whether osteoma may occur in the bone marrow remains unclear, however, this study presented the case of a patient with bone marrow osteoma located in the tibia that underwent surgical excision of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…There have been four reports of bone formation within the larynx but this has been in the context of an osteoma arising from ossified laryngeal cartilage [6][7][8][9]. Osteomas themselves are not uncommon in otorhinolaryngology, frequently arising from the skull, facial bones and paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…Osteomas themselves are not uncommon in otorhinolaryngology, frequently arising from the skull, facial bones and paranasal sinuses. Central and peripheral variants arise from a proliferation of cancellous bone in the endosteum or periosteum, respectively [9]. The extra-skeletal variant usually develops within muscle, but remains in contact with the underlying bone either by a broad base or a stalk, and therefore is not found freely within the soft tissues [10].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoma is classified into 3 types according to the site of origin. Central osteoma arises from the endosteum, peripheral osteoma originates from the periosteum, and extraskeletal osteoma develops within the muscle [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…On rare occasions, osteomas had been found in the temporal bone [ 4 ], middle ear [ 5 , 6 ], and tongue [ 7 , 8 ]. Only 4 cases of osteoma of the larynx and 2 cases of the neck have been reported thus far [ 3 , 9 – 13 ].…”
Section: Introductionmentioning
confidence: 99%